2012
DOI: 10.1002/bjs.8889
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of safety of laparoscopicversusopen appendicectomy for suspected appendicitis in pregnancy

Abstract: BackgroundLaparoscopic appendicectomy has gained wide acceptance as an alternative to open appendicectomy during pregnancy. However, data regarding the safety and optimal surgical approach to appendicitis in pregnancy are still controversial.MethodsThis was a systematic review and meta-analysis of studies comparing laparoscopic and open appendicectomy in pregnancy identified using PubMed and Scopus search engines from January 1990 to July 2011. Two reviewers independently extracted data on fetal loss, preterm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
1
23

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 45 publications
6
84
1
23
Order By: Relevance
“…The fetal death rate in non complicated appendicitis has been reported at 1.5 to 4%, but in cases of perforated appendicitis, the rate is still high at 21 to 35% [14]. In our study, open appendectomy was preferred to laparoscopic approach since it is associated with a lower rate of fetal loss as evidenced in previous two systematic reviews and meta-analysis [15,16]. Our study was conducted to detect predictors of fetal loss other than complicated appendicitis, the use of general anesthesia, operative time greater than 60 minutes; midline incision, postoperative pneumonia and hospital stay more than 3 days were found to be strong predictors of fetal loss.…”
Section: Discussionsupporting
confidence: 50%
“…The fetal death rate in non complicated appendicitis has been reported at 1.5 to 4%, but in cases of perforated appendicitis, the rate is still high at 21 to 35% [14]. In our study, open appendectomy was preferred to laparoscopic approach since it is associated with a lower rate of fetal loss as evidenced in previous two systematic reviews and meta-analysis [15,16]. Our study was conducted to detect predictors of fetal loss other than complicated appendicitis, the use of general anesthesia, operative time greater than 60 minutes; midline incision, postoperative pneumonia and hospital stay more than 3 days were found to be strong predictors of fetal loss.…”
Section: Discussionsupporting
confidence: 50%
“…Systematic review by Walsh et al (2008) found significantly high foetal loss (6 %) but lower preterm delivery rate [15]. Systematic review and meta-analysis by Wilasrusmee et al (2012) [17].…”
Section: Appendicitismentioning
confidence: 95%
“…Several systematic reviews and meta-analyses showed higher rates of fetal loss with laparoscopy as compared to open appendectomy, with the rate of fetal loss with laparoscopy approximately 5.6% versus 3.1% with open appendectomy [50, [90][91][92][93]. However, there was no difference in length of hospitalization, wound infection rate or APGAR scores between the two surgical techniques [93].…”
Section: Controversies In Surgical Managementmentioning
confidence: 99%